Case report: Inferior valved for non-valved glaucoma drainage device exchange for glaucoma control and cosmesis - Khan, Abdullah M.; Abdalla Elsayed, Maram E. A.; Malik, Rizwan (Frontiers in Ophthalmology, 2024)
IntroductionWhile the exchange of a superior valved glaucoma drainage device (GDD) for a non-valved GDD has been reported for achieving glaucoma control, inferior GDD exchange for improving the cosmetic appearance of the eyes due to poor appearance caused by encapsulated GDDs has not been previously documented. Here, we report on two patients with inferior valved GDDs who underwent an exchange for non-valved devices for glaucoma control and cosmetic improvement.Case descriptionWe report on the case of a 23-year-old gentleman and that of an 8-year-old girl, both of whom had inferior valved GDDs with uncontrolled intraocular pressure and unsightly appearance due to encapsulated GDD plates within the palpebral aperture. Both patients were unhappy about the appearance of their eyes. In each case, improvements in both glaucoma control and cosmesis were achieved by exchanging the valved GDDs for non-valved ones.ConclusionExchanging a valved for a non-valved GDD might help improve the cosmetic appearance of the eyes, in addition to providing glaucoma control.